Influence of coping with stressful situations on changes in aerobic capacity and post-workout restitution coefficient in the period of immediate preparation for the European men’s cadet wrestling championship - Jalowska, Pola; Sokołowski, Marek; Prokopczyk, Adam (Frontiers in Psychology, 2024)
The research goal of the study was to determine the relationship between coping with stressful situations and the level of aerobic capacity and post-workout restitution, as well as the changes that occur between these variables through the period of training camp preceding international men's championship competitions in age cadet. Two research hypotheses were be verified. The athletes will maintain or improve the results obtained in the performance test and the post-workout restitution coefficient during the immediate preparation period for the European Championships (H1) and the style coping with stressful situations significantly affects changes in aerobic capacity and post-workout restitution coefficient during the immediate preparation period for the European Championships (H2).The athletes of the National Men's Team of Poland in classical style wrestling (n=16). Coping with stressful situations was examined using the Coping Inventory for Stressful Situation. Aerobic capacity was analyzed using the Maximal Multistage 20-m Shuttle Run Test. The level of post-exercise restitution was calculated using the Klonowicz coefficient of restitution. Results: There was a significant increase in aerobic capacity levels (p < 0.001), a decrease in resting HR (p < 0.002), HR 1' after the test (p < 0.0031) and HR 5' after the test (p < 0.007). There was a significant correlation between emotional coping style, avoidant style focused on looking for social contacts vs. HR 3' after the test (r = 0.60; p < 0.015) and HR 5' after the test (r = 0.57; p < 0.020). In addition, a correlation was noted between avoidant style and maximum aerobic speed (r = -0.64; p < 0.008), avoidant style focused on substitute activities vs. distance and maximum aerobic speed (r = -0.72; p < 0.002).It is reasonable to implement psychological training and regular monitoring of the mental preparation into the national men's team training program athletes competing in wrestling.